Antibacterial effects of barium titanate reinforced polyvinyl-siloxane scaffolds. Issue 6 (13th April 2021) - Marin, Elia; Boschetto, Francesco; Sunthar, Thefye P. M.; Zanocco, Matteo; Ohgitani, Eriko; Zhu, Wenliang; Pezzotti, Giuseppe
Abstract: Polyvinyl-siloxane (PVS) is a modified condensation silicon that has found applications in the field of dental impression materials thanks to its high biocompatibility and the ability to be modeled on solid surfaces with a micrometric resolution. Major concerns have been raised on the possibility to sterilize PVS without distorting its geometrical shape, as immersion in antibacterial solutions often results in swelling. As a possible alternative, both radiofrequency glow discharge and UV sterilization have been successfully applied. In this paper, we focus on the possible use of a cheap, bio-compatible ceramic reinforcement powder (BaTiO3 ) to obtain a higher resistance to colonization and contribute to the prevention of bacterial infections, not only for temporary applications but also long-term. We also use a vacuum treatment to transform the composite polymer into soft scaffolds with relative densities between 35 and 65%) with similar biological properties. Testing with fractions of ceramic reinforcement up to 25% has clearly shown a beneficial effect in terms of bacteria viability against Staphylococcus epidermidis, with potential for future applications as soft biomedical scaffolds, medical clothing, sanitary materials, and filters for the sterilization of air and water. GRAPHICAL ABSTRACT: